A 10-case series of Merkel cell carcinoma in tropical Taiwan: Focusing on clinical outcomes and the interaction of oxidative stress and Merkel cell polyomavirus infections - Chia-Jui Su; Jui Lan; Chih-Hung Lee (Wolters Kluwer Medknow Publications, 2022)
Background: There are limited data discussing Merkel cell carcinoma (MCC) clinicopathological characteristics in Asian patients. Furthermore, the association between two key pathogenic factors, ultraviolet (UV) radiation and Merkel cell polyomavirus (MCPyV), remained unclear. Objectives: This study aimed to study the clinicopathological features in Taiwanese patients and to discuss the interaction between MCPyV infection and UV radiation-induced oxidative stress. Methods: We retrospectively reviewed the clinical features, pathological morphology, treatment, and outcomes of ten patients with histologically proved MCC. Eight specimens were tested for MCPyV large T-antigen. Five specimens with positive MCPyV large T-antigen were tested for 8-hydroxy-2-deoxyguanosine (8-OHdG). Results: Eight (80%) patients were male, and the median age at diagnosis was 81 years. The most common primary tumor site was extremities (8 patients, 80%), with the rest located on the head and neck region (2 patients, 20%). Intermediate type was the most common pathology subtype, with more than 70% showing reactivity to MCPyV large T-antigen. Four tumors out of 5 (80%) showed 8-OHdG positivity. Conclusion: The study showed similar demographics with previous studies in western countries but had different tumor location frequencies when compared with northeast Asia. The high frequency of UV signature oxidative stress marker, 8-OHdG in MCPyV large T-antigen-positive tumors may indicate the correlation between UV radiation and MCPyV infection. Further studies with larger numbers of patients may be required to verify its significance.